A revision of the genus Littorina (Mollusca: Gastropoda) in Korea - Yucheol Lee; Youngjae Choe; Elizabeth M. A. Kern; Yeongheon Shin; Taeho Kim; Joong-Ki Park (Animal Cells and Systems, 2018)
Littorina Férussac, 1822 is an abundant genus of small gastropods found in the upper littoral zone of rocky seashores worldwide. Although ecologically important, shell-based species identification in this genus is challenging due to phenotypic variation in shell morphology and lack of diagnostic characters among morphologically similar species. In this study, we revised the taxonomy of Korean Littorina species using morphological characters (shell and radula) and cox1 mitochondrial DNA sequences for three Korean species: L. brevicula, L. sitkana, and L. horikawai. Results suggest that L. sitkana was erroneously reported as L. kasatka in a previous study. A new record for Littorina horikawai (Matsubayashi & Habe in Habe, 1979), previously unknown from Korea, is described, which can be distinguished from L. sitkana by the presence of alternating white and brown spiral ribs on each whorl. Comparison of the mtDNA cox1 gene sequences shows very low intraspecific variation even between geographically distant populations. A phylogenetic tree supports a close relationship between L. horikawai and L. sitkana, consistent with earlier phylogenetic studies.